2022
DOI: 10.3390/medicina58040501
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Sensibility Thresholds in Implant Prosthesis, Complete Dentures and Natural Dentition: Review about Their Value in Literature

Abstract: Background and Objectives: The periodontium has important proprioceptive receptors that prevent teeth from using excessive occlusal forces during chewing. There are other receptors from adjacent tissues that replace periodontal ones when teeth are extracted and rehabilitated with prosthesis, although they seem to be less effective. Psychophysical studies investigate tactile sensibility thresholds, which are useful to measure this masticatory efficiency in different prosthetic rehabilitations. There are two typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The adjustment time in this study was shorter than reported for implant-supported crowns produced using digital and conventional workflows (Haghi et al, 2022;Joda et al, 2016). However, the adjustment time is inevitably affected by operating and subjective fac- A supra-occlusion difference of ≥50 μm is clinically relevant due to it can be both perceived by patients and detected clinically by using articulating paper (Gonzalez-Gil et al, 2022). And the prosthodontist conducting occlusal adjustment in this study is experienced, but for non-specialists, an occlusal adjustment height difference of 59 μm may take longer adjustment time.…”
Section: Mesial Adjacent Toothmentioning
confidence: 68%
See 1 more Smart Citation
“…The adjustment time in this study was shorter than reported for implant-supported crowns produced using digital and conventional workflows (Haghi et al, 2022;Joda et al, 2016). However, the adjustment time is inevitably affected by operating and subjective fac- A supra-occlusion difference of ≥50 μm is clinically relevant due to it can be both perceived by patients and detected clinically by using articulating paper (Gonzalez-Gil et al, 2022). And the prosthodontist conducting occlusal adjustment in this study is experienced, but for non-specialists, an occlusal adjustment height difference of 59 μm may take longer adjustment time.…”
Section: Mesial Adjacent Toothmentioning
confidence: 68%
“…Before occlusal adjustment, the test method caused significantly less supra‐occlusion in MIP and led to less occlusal adjustment than the control method. A supra‐occlusion difference of ≥50 μm is clinically relevant due to it can be both perceived by patients and detected clinically by using articulating paper (Gonzalez‐Gil et al, 2022). And the prosthodontist conducting occlusal adjustment in this study is experienced, but for non‐specialists, an occlusal adjustment height difference of 59 μm may take longer adjustment time.…”
Section: Discussionmentioning
confidence: 99%